The Role of Family Social Support in Academic Burnout among Islamic Students : The Mediating Role of Student Engagement - Azizah, Fitri Rizkiah Nur; Na'imah, Tri; Dwiyanti, Retno; Grafiyana, Gisella Arnis (Psychocentrum Review, 2025)
Abstract. Family social support plays a vital role in enhancing student engagement in learning, thereby minimizing the risk of academic burnout. This study aims to analyze the effect of family social support on academic burnout, with student engagement serving as a mediator, among islamic students. The research employs a quantitative approach, targeting the student population of one of islamic school in Ciamis. The sample, comprising 181 students aged 13 to 16 years (male and female), was selected using a proportionate stratified random sampling technique. The instruments used in this study include the Family Social Support Scale, the Student Engagement Scale (SES), and the Maslach Burnout Inventory Student Survey (MBI-SS). Data analysis was conducted using SmartPLS 4.0 software, which involved testing the outer and inner models. The results of the analysis indicate t-statistics of 5.549 > 1.96 and p-values of 0.00 < 0.05, confirming that the hypothesis is accepted. This finding demonstrates that family social support significantly affects academic burnout, with student engagement acting as a mediator among islamic students.